Pengaruh Mekanisme Corporate Governance Terhadap Kinerja Keuangan Perusahaan Pada Sektor Perbankan Periode 2020-2022 Yang Terdaftar Di BEI - Royen Pandapotan Munthe; Danri T Siboro; Ardin Dolok Saribu (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to explore the relationship between corporate governance mechanisms and the financial performance of the banking industry in Indonesia for the 2020-2022 period. In this research the dependent variable is financial performance (ROA) and the independent variables used are audit committee, independent board of commissioners, managerial ownership. The sample used in this research is banking companies listed on the Indonesia Stock Exchange (BEI) for the 2020-2022 period. The sampling technique in this research was carried out using a purposive sampling method so that 26 companies were obtained. This research uses secondary data and the research method used is multiple linear regression analysis. From the results of hypothesis testing it can be concluded that only the first hypothesis (audit committee) is proven to have a positive and significant effect on financial performance, while the board of commissioners and managerial ownership have no and insignificant effect on the dependent variable. This is shown through the results of the t-test which shows a significant relationship with the variables with a significance level of 5%.